MORRIS’ SEMIOTIC IN RELIGION PERCEPTION AND CONCEPTION IN GANE OF POLINAKI TRADITIONAL WEDDING RITUAL IN KULAWI ETHNIC - Indah Lestari; Burhanuddin Arafah; Harlinah Sahib; Mustafa Makka (Universitas Islam Sumatera Utara (UISU), 2020)
The purpose of this research is to examine the concept of religion in Gane, a ritual speech which is still alive and practiced by Kulawi ethnic in Sigi regency, Central Sulawesi. Nowadays, Gane ritual speech is no longer in demand by most of the Kulawi ethnic, especially the educated young generation, because they have been eroded by the influence of modernization and globalization in addition to the influence of the entry of religion held by the majority of the Kulawi ethnic today and modern education. The text of Gane is obtained from a ritual speech named Polinaki which is contained in traditional wedding in Kulawi. The text is analyzed qualitatively using behavioral semiotic approach proposed by Charles Morris. Behavioral semiotic is creating a particular action or behavior to achieve a certain goal and applying syntactic, semantic, and pragmatic dimensions for analyzing a text. The results show that in syntactic dimension, Gane is a text with literary style consisting of unique characteristics in terms of structure, function, and meanings. In semantic dimension, Gane holds contextual, emotive, conative, and poetic meanings observed through its function. In pragmatic dimension, the impacts of Gane influence the perception and conception of religion.